THE ROLE OF TRADE BARRIERS IN INTERNATIONAL TRADE IN METALLURGICAL INDUSTRY OF UKRAINE - Fato Sharoian (Three Seas Economic Journal, 2021)
The purpose of the paper is to analyze and present the role of the metallurgical industry for the economy of Ukraine and evaluate the impact of trade restrictions on the international activity of the metallurgical industry of Ukraine. As a result, this study evaluated the risks of international activities of metallurgical enterprises of Ukraine with key partner countries. Methodology. Assessment of the role of the metallurgical industry for the Ukrainian economy and the extent of the impact of trade barriers on international activities is based on several statistical data and a few methods and rules for their analysis. Their use will allow managers of metallurgical companies to form a strategy for the development of the enterprise in international markets and quickly respond to changes in the external market situation. These methods include statistical analysis, strategic segmentation, deductive and inductive methods, data comparison method, forecasting and risk assessment. Results. Per capita steel consumption growth rates have shown positive dynamics since 2010. Volatility levels of per capita steel consumption of the population is significantly lower than the growth of world GDP. Against the backdrop of slowing global GDP growth rate of steel consumption continues to grow. According to the level of consumption of steel per capita, the author singled out three stages in the development of countries. The share of exports of products of the metallurgical industry of Ukraine in 2020 amounted to 18.3% in monetary terms. This indicator is the second after the volume of exports of agricultural products. Among the total export of steel products in Ukraine 95% are engaged in export of ferrous metals, which is a raw product. The trade balance of Ukraine in the trade of metallurgical products has been decreasing since 2018 amid a decrease in export volumes and has not yet reached the level of 2016. According to the World Trade Organization, at the end of 2020, there were 3,208 non-tariff trade barriers in the world regarding trade in metals and metal products. In terms of the number of anti-dumping measures, the market of metals and metal products ranks first – 843 measures out of 2160 measures for all product groups. This tool is used by countries to protect the domestic market and as a tool in international competition. As a result of a matrix analysis of the rates and volumes of growth of Ukraine's metallurgical products in the context of partner countries and the number of introduced trade barriers, the countries with the highest risk in international activities and the most promising sales markets were identified. The Russian Federation and the United States are identified as the countries with the highest risk of the impact of trade barriers on international activities for Ukrainian metallurgical companies. The most promising sales markets are Saudi Arabia and Italy. Practical implications. With the help of the results of this paper, managers of metallurgical enterprises in Ukraine can form and adjust the strategic directions for the development of companies in the frame-work of international activities.